MiRNAs as non-invasive biomarkers in the serum of Oral Squamous Cell Carcinoma (OSCC) and Oral Potentially Malignant Disorder (OPMD) patients. (March 2023) - Mazumder, Sayani; Basu, Baidehi; Ray, Jay Gopal; Chatterjee, Raghunath
Abstract: Objective: Cell-free microRNAs have shown differential levels in the serum of individuals under disease conditions suggesting its potential to act as biomarkers. A population specific miRNA signature in oral cancer is reported in different studies. We aim to identify a set of serum specific miRNAs that may differentiate oral cancer, oral pre-malignant conditions from the healthy individuals. Design: We investigated the levels of 24 miRNAs in the serum of 47 Oral squamous cell carcinoma (OSCC) patients, 20 patients with Oral potentially malignant disorders (OPMD) and 42 healthy controls from Eastern India. Small RNAs were isolated from serum samples followed by cDNA synthesis. Levels of miRNAs were determined using qRT-PCR. The sources of serum specific miRNAs were evaluated using GTEx-RNAseq and TCGA-HNSCC database. Results: Five miRNAs, miR-483–5p, miR-31–5p, Let-7b-5p, miR-486–5p and miR-30e-5p showed significant elevation in OSCC patients. An Elastic-Net model with 4 miRNAs classified OSCC from healthy controls with 80 % sensitivity, 64.3 % specificity, and 72.4 % accuracy. Mir-483–5p and miR-31–5p was significantly overexpressed in OSCC tissues as well as significantly higher in the serum of Leukoplakia and Verrucous carcinoma patients suggesting their potential as early disease markers. MiR-483–5p showed a consistent elevated level in the serum/plasma of oral cancer patients across different population and was found to be tumour specific while, the rest of the miRNAs showed variable results across different studies. Conclusions: Our study suggested that the serum miRNAs in oral cancer and pre-malignant disorder conditions can be used as a non-invasive marker for screening of these oral conditions. Highlights: Five miRNAs were significantly elevated in the serum of OSCC patients than controls. Elastic-net model with serum miRNAs can be used to detect OSCC with 72.4 % accuracy. MiR-483–5p and miR-31–5p were significantly high in both OSCC and OPMD patients. MiRNAs with tumor tissue as possible source may serve as noninvasive marker in OSCC.